When research animals become pets and pets become research animals: care, death, and animal classification - Palmer, A; Skidmore, T; Anderson, A (Taylor and Francis, 2022)
This paper explores what happens to care, and decisions about ending and extending life, when research animals become pets and pets become research animals. To do this, we draw on in-depth qualitative research on (i) rehoming of laboratory animals, (ii) veterinary clinical research, and (iii) the role of the Named Veterinary Surgeon (NVS) in UK animal research. We begin by exploring how (in theory and practice) the ethical, affective, and practical elements of care are split in the research laboratory. We then investigate arguments for and against ending and extending animal life via clinical research and rehoming, highlighting how these activities bring norms and dilemmas around animal death in the laboratory and veterinary clinic to the fore. We conclude by demonstrating the value of investigating borders between animal categories for understanding dilemmas around care and death, and for contributing to emerging literatures within geography around animal care, death, and categorisation. Key contributions of our work include highlighting: how care roles can be split; the importance of considering speculative and in-practice elements of care; the contextdependency and multiplicity of practices of killing in the veterinary clinic and laboratory; and the flexibility and changing nature of animal categories.